Changes In Indonesian Phonology In The Medan Dialect: Generative Analysis - Khairiah Zahra; Zahira Shofa Sihotang; Yani Lubis (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
Indonesian is one of the many dialects of Malay. Therefore, High Malay (Melaka/Riau) is used as the basic language of Indonesia. Even though more than 90% of Indonesians are able to understand and speak the language, most Indonesians do not regard their mother tongue as Indonesian. The most common "Indonesian" idiom is associated with situations where a standard variety of Indonesian is spoken official. The local dialect is the language most commonly used in daily interactions among native speakers. People in the Medan area, like other cities, usually speak a dialect of Indonesian which is called the dialect, and the phonological system has recently undergone some changes. This study aims to analyze and display the system of lexical changes in Indonesian spoken by the people of Medan.This paper uses descriptive-quantitative methodology and generative phonological theory in its preparation. The data for this study came from written sources such as journals and articles about the history of changes in phoneme systems, as well as oral sources such as those written by native speakers of the Medan language. The results of this study indicate that generationally, the people of Medan generally remove or change certain phonemes in the words they speak, such as the a and u phonemes in the word "chaotic" which disappear and become o. in the word "kaco." The word "ask" finally develops into the word "ask" by adding the last word as a phoneme. This indicates that many words in Indonesian have different pronunciations when spoken by the people of Medan, and this will be analyzed and presented in more detail in the following sections.